(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
This paper discusses the application and applicability of data analytics in accounting and auditing. At the present rate of technological development, identification and management of financial risks have emerged as a key role for organizations. This research discusses the application of data analytics tools for preemptive risk identification, audit analysis, and enhancing decision-making efficiency. Additionally, it discusses the current practices in Uzbekistan today and provides constructive recommendations for improvement